The Language Relativity on Students' Essay Writing by Utilizing Mind Mapping Technique in EFL Learning - Moh. Hafidz; Siti Maria Ulfa (Edulitics (Education, Literature, and Linguistics) Journal, 2023)
This article discusses essay writing techniques, preposition and transitional words, and terms that cannot be lexically or syntactically comprehended but can be culturally understood. The purpose of this study is to discover language relativity in students' essay paragraphs utilizing a mind mapping technique in EFL learning. The researcher employed a descriptive strategy, observing and documenting the writing process in class. The participants were distinguished by their diverse living, educational, and professional backgrounds. These writings were descriptively assessed using appropriate literature, and observations were also undertaken to arrive at a reasonable interpretation. As a result, mind mapping with language relativity integrates meaningful students' knowledge such as history, linguistics such as preposition and transition word usage, and Indonesian cultural types and values such as Sarabi, Gempol Ice, and Rujak Cingur are Indonesian iconic culinary to organize and structure into essay writing fluently in EFL learning.